2013
DOI: 10.3324/haematol.2013.085076
|View full text |Cite
|
Sign up to set email alerts
|

Common variable immunodeficiency and idiopathic primary hypogammaglobulinemia: two different conditions within the same disease spectrum

Abstract: ABSTRACTical practice, but information concerning the prevalence and the clinical and immunological characteristics is not available. It is important to obtain insight into the frequency and severity of the clinical complications of IPH, to clarify whether IPH is a clinically relevant antibody deficiency, and to develop appropriate treatment strategies. In addition, analysis of immunological parameters will enable the comparison of pathophysiological aspects of IPH and CVID.Therefore, we aimed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 16 publications
7
55
1
Order By: Relevance
“…respiratory infections, bronchiectasis) but did not show the non-infectious complications (autoimmune cytopaenia, polyclonal lymphocytic proliferation and persistent enteropathy) [12], which have been linked to increased mortality [10,13]. In our study, autoimmune disease, polyclonal lymphocytic proliferation and enteropathy were reported in a minority of the total group of hypogammaglobulinaemias (4%).…”
Section: Discussionmentioning
confidence: 71%
“…respiratory infections, bronchiectasis) but did not show the non-infectious complications (autoimmune cytopaenia, polyclonal lymphocytic proliferation and persistent enteropathy) [12], which have been linked to increased mortality [10,13]. In our study, autoimmune disease, polyclonal lymphocytic proliferation and enteropathy were reported in a minority of the total group of hypogammaglobulinaemias (4%).…”
Section: Discussionmentioning
confidence: 71%
“…25 The samples were divided over five age categories, namely the newborns (samples from the umbilical cords, UC), the very young children (age 0.1 to 3.9), the young children (age 4 to 9.9), the adolescents (10-17) and the young adults (age 20 to 40; Table 1). In addition to the biological samples, 30 pooled plasma standards (Visucon-F frozen normal control plasma; Affinity Biologicals 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 99, Ancaster, Canada) and 12 PBS blanks were included in the cohort to serve as positive and negative controls.…”
Section: Cohortmentioning
confidence: 99%
“…Rather, these patients display defects in both CD27 Ï© IgM Ï© IgD Ï© and CD27 Ï© IgD-, or only CD27 Ï© IgD-B cells. 8 Thus, further studies are required to assess the nonredundant role of CD27 Ï© IgM Ï© IgD Ï© B cells in human immunity.…”
mentioning
confidence: 99%